TG, DSC, XRD, and SEM studies of the substituted lithium ferrite formation from milled Sm2O3/Fe2O3/Li2CO3 precursors; Journal of Thermal Analysis and Calorimetry; Vol. 148 - Lysenko E. N. Elena Nikolaevna; Vlasov V. A. Vitaliy Anatolievich; Nikolaeva S. A. Svetlana Andreevna; Nikolaev E. V. Evgeny Vladimirovich (2023, 2023)
Title screen